2003
DOI: 10.1021/la034440q
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinylidene fluoride) with Grafted Zwitterionic Polymer Side Chains for Electrolyte-Responsive Microfiltration Membranes

Abstract: Thermally induced molecular graft copolymerization of the zwitterionic monomer, N,N′-dimethyl-(methylmethacryloyl ethyl)ammonium propanesulfonate (DMAPS), with the ozone-preactivated poly-(vinylene fluoride) (PVDF) was carried out in a mixed solvent of N-methyl-2-pyrrolidone (NMP) and dimethyl sulfoxide (DMSO). The chemical composition of the resulting PVDF with grafted DMAPS polymer (PDMAPS) side chains, or the PDMAPS-g-PVDF copolymers, was analyzed by elemental analysis. An increase in the [DMAPS]/[-CH2CF2-]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
81
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 39 publications
0
81
0
Order By: Relevance
“…They have been shown to be highly resistant to biomolecular fouling due to their high degree of hydration [32][33][34][35][36][37]. Since this discovery, many researchers have improved the fouling resistance of membranes by attaching zwitterionic groups on their surface, by post-processing existing membranes [38][39][40][41][42][43][44] or by using zwitterionic surface-segregating additives [45][46][47]. Two studies incorporated zwitterionic groups in charged hydrogel layers to boost fouling resistance [48,49].…”
Section: Introductionmentioning
confidence: 99%
“…They have been shown to be highly resistant to biomolecular fouling due to their high degree of hydration [32][33][34][35][36][37]. Since this discovery, many researchers have improved the fouling resistance of membranes by attaching zwitterionic groups on their surface, by post-processing existing membranes [38][39][40][41][42][43][44] or by using zwitterionic surface-segregating additives [45][46][47]. Two studies incorporated zwitterionic groups in charged hydrogel layers to boost fouling resistance [48,49].…”
Section: Introductionmentioning
confidence: 99%
“…Sulfobetaine (SB) and its polymer (PSB) have been used to functionalize porous membranes due to the strong hydration and environment sensitivity [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Yang et al prepared antibiofouling polypropylene MF membrane by the surface hydrophilization with PSB [13].…”
mentioning
confidence: 99%
“…Yang et al prepared antibiofouling polypropylene MF membrane by the surface hydrophilization with PSB [13]. Zhai et al observed that the permeate flux of aqueous solutions through the PSB-g-poly(vinylidene fluoride) (PVDF) MF membranes decreased as the electrolyte concentration of the permeate solution increased [14]. Zhao et al used the PSB-gcellulose membrane to purify bovine serum album (BSA) from polystyrene nanoparticles (NPs) of different sizes by altering the concentration of NaCl in the solutions [12].…”
mentioning
confidence: 99%
“…The design, synthesis and development of new functional materials were studied to provide suitable materials for biomedical applications such as polyacrylate, polyester, polyurethane, polyamide, polyimide, polyester, polynorborene, polytetrafluoroethylene, polydiphenylacetylenes and polymeric resins . Also, surface modification technology was considered to change the surface microenvironment of the materials [22][23][24][25][26]. Therefore, a suitable material and fabrication process can be selected, designed and established.…”
Section: Introductionmentioning
confidence: 99%